Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 196968 by sonukgindia last updated on 05/Sep/23

Answered by MM42 last updated on 05/Sep/23

if  x,y∈ R   { ((5s−p=10+7(√3))),((s^2 −2p=7)) :}  ⇒s^2 +10s−27−14(√3)=0  ⇒s=2+(√(3 ))⇒p=2(√3)   ⇒X^2 −(2+(√3))X+2(√3)=0  ⇒x=(√(3  ))& y=2

$${if}\:\:{x},{y}\in\:\mathbb{R} \\ $$$$\begin{cases}{\mathrm{5}{s}−{p}=\mathrm{10}+\mathrm{7}\sqrt{\mathrm{3}}}\\{{s}^{\mathrm{2}} −\mathrm{2}{p}=\mathrm{7}}\end{cases} \\ $$$$\Rightarrow{s}^{\mathrm{2}} +\mathrm{10}{s}−\mathrm{27}−\mathrm{14}\sqrt{\mathrm{3}}=\mathrm{0} \\ $$$$\Rightarrow{s}=\mathrm{2}+\sqrt{\mathrm{3}\:}\Rightarrow{p}=\mathrm{2}\sqrt{\mathrm{3}}\: \\ $$$$\Rightarrow{X}^{\mathrm{2}} −\left(\mathrm{2}+\sqrt{\mathrm{3}}\right){X}+\mathrm{2}\sqrt{\mathrm{3}}=\mathrm{0} \\ $$$$\Rightarrow{x}=\sqrt{\mathrm{3}\:\:}\&\:{y}=\mathrm{2} \\ $$$$ \\ $$

Answered by Frix last updated on 05/Sep/23

ax+xy+ay=b  x^2 +y^2 =c  x=u−v∧y=u+v  u^2 +2au−v^2 =b ⇒ v^2 =u^2 +2au−b  2u^2 +2v^2 =c ⇒ v^2 =(c/2)−u^2   u^2 +2au−b=(c/2)−u^2   u^2 +au−((2b+c)/4)=0  u=−(a/2)±((√(a^2 +2b+c))/2)  v=(√(−((2a^2 +2b−c)/4)±((a(√(a^2 +2b+c)))/2)))    With a=5∧b=10+7(√3)∧c=7 we get  x=(√3)∧y=2  x=−6−((√3)/2)−((√(33+24(√3)))/2)i∧y=−6−((√3)/2)+((√(33+24(√3)))/2)i  ...and of course we can exchange x↔y

$${ax}+{xy}+{ay}={b} \\ $$$${x}^{\mathrm{2}} +{y}^{\mathrm{2}} ={c} \\ $$$${x}={u}−{v}\wedge{y}={u}+{v} \\ $$$${u}^{\mathrm{2}} +\mathrm{2}{au}−{v}^{\mathrm{2}} ={b}\:\Rightarrow\:{v}^{\mathrm{2}} ={u}^{\mathrm{2}} +\mathrm{2}{au}−{b} \\ $$$$\mathrm{2}{u}^{\mathrm{2}} +\mathrm{2}{v}^{\mathrm{2}} ={c}\:\Rightarrow\:{v}^{\mathrm{2}} =\frac{{c}}{\mathrm{2}}−{u}^{\mathrm{2}} \\ $$$${u}^{\mathrm{2}} +\mathrm{2}{au}−{b}=\frac{{c}}{\mathrm{2}}−{u}^{\mathrm{2}} \\ $$$${u}^{\mathrm{2}} +{au}−\frac{\mathrm{2}{b}+{c}}{\mathrm{4}}=\mathrm{0} \\ $$$${u}=−\frac{{a}}{\mathrm{2}}\pm\frac{\sqrt{{a}^{\mathrm{2}} +\mathrm{2}{b}+{c}}}{\mathrm{2}} \\ $$$${v}=\sqrt{−\frac{\mathrm{2}{a}^{\mathrm{2}} +\mathrm{2}{b}−{c}}{\mathrm{4}}\pm\frac{{a}\sqrt{{a}^{\mathrm{2}} +\mathrm{2}{b}+{c}}}{\mathrm{2}}} \\ $$$$ \\ $$$$\mathrm{With}\:{a}=\mathrm{5}\wedge{b}=\mathrm{10}+\mathrm{7}\sqrt{\mathrm{3}}\wedge{c}=\mathrm{7}\:\mathrm{we}\:\mathrm{get} \\ $$$${x}=\sqrt{\mathrm{3}}\wedge{y}=\mathrm{2} \\ $$$${x}=−\mathrm{6}−\frac{\sqrt{\mathrm{3}}}{\mathrm{2}}−\frac{\sqrt{\mathrm{33}+\mathrm{24}\sqrt{\mathrm{3}}}}{\mathrm{2}}\mathrm{i}\wedge{y}=−\mathrm{6}−\frac{\sqrt{\mathrm{3}}}{\mathrm{2}}+\frac{\sqrt{\mathrm{33}+\mathrm{24}\sqrt{\mathrm{3}}}}{\mathrm{2}}\mathrm{i} \\ $$$$...\mathrm{and}\:\mathrm{of}\:\mathrm{course}\:\mathrm{we}\:\mathrm{can}\:\mathrm{exchange}\:{x}\leftrightarrow{y} \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com